Analysis of non-rainy attenuation on earth-space path in Ota, Southwest Nigeria. (May 2017) - Omotosho, T V; Akinwumi, S A; Usikalu, M R; Ometan, O O; Adewusi, M O; Abdullah, M
Abstract: Propagation effects due to atmospheric gases and tropospheric scintillation requires accurate modelling in the design of satellite communication systems. The combination of the two attenuation phenomena was observed within the period of August 2014 to December 2015. The result of this paper presents the on-going observation and data analysis of non-rainy attenuation on earth-space path in Ota, Southwest Nigeria. Results of clear-sky attenuation vary between 0 dBm and 4.85 dBm in January and February 2015 respectively. While a value of 4.23 dBm and 4.75 dBm were observed in October 2014 and 2015 respectively. The results will be useful for satellite communication system design and will be submitted to ITU-R Study group 3 Databank.